Social inequality and social injustice : - Kallen, Evelyn (Palgrave Macmillan, 2003)
This book uses a human rights framework to analyze how group-level social inequalities and injustices are socially constructed and maintained through violations of human rights on grounds of race, gender, sexuality, etc., and how human rights legislation can help such violations to effectively be redressed. Although it focuses primarily on democratic nations, it uses international case material to highlight key global issues.